2016
DOI: 10.4236/ojas.2016.61008
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Organic and Inorganic Selenium on Liver Glycogen and Lactate, pHu, Color and Drip Loss of Chicken <i>Pectoralis</i> and <i>Gastrocnemius</i> Muscles

Abstract: The effect of selenium supplementation in finishing broiler diets on meat quality was studied. A corn soya based diet was supplemented with 0.3 ppm of Se from an organic (Seleno methionine; Se-Met) or inorganic source (sodium selenite; Se-Na) and offered to Rossmale chickens from thirty five to fifty two days old. Body weight and feed consumption were recorded during the experimental period. Immediately post sacrifice liver was removed and weight was recorded. The liver glycogen and lactate content was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was found that the addition of Se to the diet enhances the water-holding capacity, improves the profile of fatty acids, affects the stability of heme dyes and increases the shelf life of meat and its enrichment with Se (Mateo et al, 2007). The addition of SeMet may reduce the free leakage of water from the meat, which is an important aspect in terms of the culinary suitability of the obtained raw material (del Puerto et al, 2016). The concentration of Se in the muscles of chicken depends on the SeMet content in the chickens diet.…”
Section: Selenium and Product Quality In Poultrymentioning
confidence: 99%
“…It was found that the addition of Se to the diet enhances the water-holding capacity, improves the profile of fatty acids, affects the stability of heme dyes and increases the shelf life of meat and its enrichment with Se (Mateo et al, 2007). The addition of SeMet may reduce the free leakage of water from the meat, which is an important aspect in terms of the culinary suitability of the obtained raw material (del Puerto et al, 2016). The concentration of Se in the muscles of chicken depends on the SeMet content in the chickens diet.…”
Section: Selenium and Product Quality In Poultrymentioning
confidence: 99%